2018
DOI: 10.1186/s11782-017-0022-6
|View full text |Cite
|
Sign up to set email alerts
|

Ranking and selecting the best performance appraisal method using the MULTIMOORA approach integrated Shannon’s entropy

Abstract: The selection process of appropriate Performance Appraisal (PA) methods for organizations in today's dynamic and agile environments along with its funding scales is a complex problem. Performance appraisal in modern organizations has become a part of the strategic approach toward integrating business policies and human resource activities. The existence of multiple criteria in the decision-making procedure makes finding the optimal PA method more challenging. The current study tackles a PA method assessment by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 57 publications
0
32
0
3
Order By: Relevance
“…Stević et al [43] applied a hybrid novel MCDM methodology including DEMATEL, EDAS, COPRAS and MULTIMOORA methods in a supplier selection problem in regard to a construction organization. Maghsoodi et al [44] suggested an application of the MULTIMOORA approach integrated with Shannon's entropy in ranking and selecting the best performance appraisal method in an organization in Iran. Maghsoodi et al [45] proposed a combinative approach called cluster analysis for improving multiple criteria decision analysis (CLUS-MCDA) including the k-means clustering technique and MULTIMOORA method in order to tackle a big data supplier selection problem in an ICT company in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…Stević et al [43] applied a hybrid novel MCDM methodology including DEMATEL, EDAS, COPRAS and MULTIMOORA methods in a supplier selection problem in regard to a construction organization. Maghsoodi et al [44] suggested an application of the MULTIMOORA approach integrated with Shannon's entropy in ranking and selecting the best performance appraisal method in an organization in Iran. Maghsoodi et al [45] proposed a combinative approach called cluster analysis for improving multiple criteria decision analysis (CLUS-MCDA) including the k-means clustering technique and MULTIMOORA method in order to tackle a big data supplier selection problem in an ICT company in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…From the theory and application levels, Karel, Brauers, and Zavadskas (2012) illustrated the superiority of MULTIMOOA, comparing it with other widely used MADM methods, such as ELECTRE, TOPSIS, and AHP. Due to the simplicity and effectiveness, the MULTIMOORA method has been applied to various purposes, such as the ranking of European Union member states (Brauers, Baležentis, & Baležentis, 2011), materials selection (Hafezalkotob & Hafezalkotob, 2015), and appraisal methods selection (Maghsoodi, Abouhamzeh, Khalilzadeh, & Zavadskas, 2018). MULTIMOORA is previously integrated with various kinds of weighting methods such as Entropy (Hafezalkotob & Hafezalkotob, 2016).…”
Section: The Ranking Methodsmentioning
confidence: 99%
“…Unlike a majority of statistical methods based on normal distribution, entropy-based statistics is applicable to any distribution and even in cases when distributions are a priori unknown Maruyama, et al [3]. It has been commonly used in physics [4,5], chemistry [6,7], informatics [8] and bioinformatics [2,9,10], image processing [11,12], for the evaluation of business organisations [13], economics and finance processes [14] and company systems performance [15,16]. The concept has been used also for the analysis of urban ecosystems [17], environmental analysis [3,[18][19][20], medical records [21][22][23] and in scientometrics [24,25].…”
Section: Introductionmentioning
confidence: 99%